Seismic resistance capacity of beam column connections in high-rise buildings E-Defense shaking table test. - Chung, Yu-Lin
A series of E-Defense shaking table tests are conducted on a large-scale test specimen that represents a high-rise steel building. Two types of connections featuring the connection details commonly used in 1970s, in the early days of high-rise construction in Japan, are adopted: the field-welded connection consisting of welded unreinforced flanges and a bolted web type, and the shop-welded connection in which the flanges and web are all-welded to the column flange in the shop. To examine the seismic capacity of a total of 24 beam-to-column connections of the specimen, particularly when it is subjected to long-period ground motion characterized not so much by large amplitude as by very many cycles of repeated loading, the test specimen is shaken repeatedly until the connections fractured. The test results indicate that a few of the field-welded connections fractured from the bottom flange weld boundary in a relatively small cumulative rotation primarily due to the difficulties in ensuring the welding and inspection performance in the actual field welding. The shop-welded connections are able to sustain many cycles of plastic rotation, with an averaged cumulative plastic rotation of 0.86 rad. Two shop-welded connections exhibit ductile fractures but only after experiencing many cycles. The presence of RC floor slabs promotes the strain concentration at the toe of the weld access hole in the bottom flange by at least twice compared with the case without the slab, which had resulted in a decrease in the cumulative plastic rotation by about 50%.
Keywords: High-rise building; Long-period ground motion; Beam-to-column connection; Composite action